Measurement of pinch grip forces during sport climbing - Fuss, F. K.; Niegl, G.; Yap, Y.; Tan, M. (The Engineering of Sport 5, Volume 2, 2004)
An instrumented pinch grip handhold was developed, which allows for placement of the fingers on the upper surface and the thumb on the lower surface. Both surfaces have curvatures modeled after third-order polynomials. Each half of the hold is connected to two 3D piezoelectric force transducers in order to measure the finger and thumb forces separately. The instrumented hold was tested during climbing at a frequency of 100 Hz. For both the upper and lower halves of the hold, the force and moment equilibrium were calculated, and the positions of the instantaneous centers of pressure on the two third-order polynomial surfaces were determined. The following parameters were obtained from data analysis of the fingers and thumb separately, contact time, mean resultant force, relative friction (ratio of tangential and normal forces), and smoothness factor. Finally, the vector diagrams were developed for both fingers and thumb. In the pinch grip, the force of the thumb is about 1/5 -1/4 of the finger force. The friction at the thumb is 2-3 times higher than that of the fingers. Friction and forces on fingers and thumb increase with the wall inclination; the finger forces increase more than the thumb forces do.